Variability in grain quality attributes of high yielding rice varieties (Oryza sativa L.) of diverse origin - Vanaja, T.; Babu, Luckins C. (Journal of Tropical Agriculture, 2007)
Genetic variability of 10 quality parameters in a set of 56 high yielding diverse rice genotypes was evaluated. Phenotypic and genotypic coefficients of variation revealed the existence of large variability in alkali-spreading value and moderate variability in L/B ratio of grain, milling percentage, amylose content, water uptake, and volume expansion. All quality attributes exhibited high broad sense heritability. High heritability, high expected genetic gain, and moderate genotypic coefficient of variation were noted for alkali spreading value, L/B ratio of grain, milling percentage, amylose content, volume expansion ratio, and water uptake, implying the potential of these parameters to be used in breeding programmes.